It's Not Fair! Are Applicant Reactions to Personal and Professional Social Media Screenings Similar?. Issue 3 (8th August 2022) - Armenteros, Natalie; Hatem, Aniqa; Heron, Laura Mary; Viswesvaran, Chockalingam
ABSTRACT: The use of social media in selection processes to gather information about job candidates is a heavily debated and controversial topic. However, research that focuses on whether applicant reactions differ when social networking sites (SNSs) are screened is limited. This study used a quasi-experimental design to examine perceptions of face validity, predictive validity, and test fairness when personal (Facebook or Twitter) versus professional (LinkedIn) profiles are screened. The moderating role of self-monitoring was also explored. Findings demonstrated that applicants react negatively to screenings involving personal SNSs. High self-monitors had favorable face validity and predictive validity reactions to a professional SNS screening, but the opposite effect was found for personal SNSs. Practical implications for organizations and future directions for research are discussed.